MEANINGS IN THE PROCESS OF SIGNIFICATION OF LANCÔME’S BEAUTY SERUM ADVERTISEMENTS - Cliff Albert Tuna; Esther H Kuntjara (Institute of Research and Community Outreach - Petra Christian University, 2017)
Through this study, the writer aimed to find out how meanings are created in advertisements video. The three objectives of this study are to find out how meanings are created through verbal expressions, how the visual expressions of the advertisements support the verbal expressions and to find out the differences between the two advertisements. The data used to conduct this study were Lancôme Génifique Serum Advertisement (2009) and Lancôme Advanced Génifique Serum (2013). After analyzing the data with the research questions in mind, the writer found out that meanings in both advertisements are created through the verbal captions and what were visually shown on the advertisement videos. The writer also found out that there were a few differences between the first and second advertisements. The second advertisement provides more appealing visuals, more direct and convincing verbal expressions and more facts and needed information regarding the promoted product. These factors make the second advertisement an improved version of the first one.